Classification of land use and land cover on three cattle farms within the buffer zone of the Río Plátano Biosphere Reserve, Honduras - Lainez S., Andrea N. (Zamorano: Escuela Agrícola Panamericana, 2023)
In the last few decades changes in land use and land cover (LULC) have created pressure on natural ecosystems, altering their processes. This phenomenon is evident in the Rio Plátano Biosphere Reserve, where the expansion of the agricultural frontier within the buffer zone has created pressure on its natural resources, generating concern. This is why this descriptive, non-experimental study was done. The main objective of the study was to classify LULC on three cattle farms within the buffer zone of the reserve, to quantify them and establish a baseline for future monitoring. To achieve this, a photointerpretation analysis using multispectral and RGB images captured by an EbeeAg® drone was done. Subsequently, the Pix4D® software was used for the primary processing of the images. Furthermore, the classification process for LULC, the by-products, and the cartographic design of the maps were generated with the ArcGIS® and Surfer® software tools. Finally, a flight protocol and pre-processing images manual was made. As a result, a total of 12 land use and land cover classes were created and, an average of moderate to abundant vegetation cover and a slope range from 15-60% on the cattle farms were found. It is concluded that within the three farms the predominant land use was pasture and Nueva Esperanza was the farm with the most abundant tree cover (23.52%). Finally, those maps can be a valuable information for the generation of a land use capability classification of the cattle farms.
Keywords: Land cover; land use; livestock; photointerpretation; protected area